Histochemical observations on circumvallate papillae and associated glands in tongue of sheep - PAWAR, H S; SINGH, JASWANT; ROY, K S (The Indian Journal of Animal Sciences, 2013)
The phosphatase in gustatory epithelium of sheep circumvallate papillae revealed site-specific histochemical localization of AKPase, ACPase and ATPase was mainly localized in taste bud cells. The presence of various phosphatases, esterases and oxidorcductascs in superficial byer of moat indicated aphysiologically active stratum comeum. Papillae-associated glundular parenchyma also revealed strong activities of AKPase, ATPasc, SDH, LDH and NADPH .